A Practical and Safe Parameter for Determining Gestational Age: Transverse Cerebellar Diameter - Muhammed Alpaslan (Van Tıp Dergisi, 2023)
INTRODUCTION: We aimed to investigate the role of transcerebellar diameter (TCD) on obstetric ultrasound for calculating the fetal gestational age METHODS: The women with a pregnancy of 18-25 weeks (according to date of the last menstrual period(LMP)) who underwent a obstetric ultrasound were included in the study. The biparietal diameter (BPD), femur lenght (FL) and trans-cerebellar diameter (TCD) were calculated and their correlation with the getastional age were examined with statistical analysis. RESULTS: Our study was conducted on 114 pregnant women. The mean age was 27 (+-5-17) and approximately 54% of them were between 21-22 weeks. The value of TCD in millimeters in transabdominal ultrasonography showed a strong positive correlation with LMP(r=0.916, p<0.001), BPD(r=0.939, p<0.001) and FL(r=0.880, p<0.001) at 18-25 weeks in indicating gestational age. As the gestational age increased, TCD also increased. In addition, the value of TCD in millimeters was the same as the gestational age in approximately 80% of all patients, especially when compared with BPD. DISCUSSION AND CONCLUSION: Because TCD calculation on obstetric ultrasound between 18-25 week of gestation is a safe and easy method for evaluating the general condition of fetüs, it may be added to BPD, FL calculation in the routine practise.